Visualizing transfer of microbial biomolecules by outer membrane vesicles in microbe‐host‐communication in vivo. Issue 12 (19th October 2021) - Bittel, Miriam; Reichert, Patrick; Sarfati, Ilann; Dressel, Anja; Leikam, Stefanie; Uderhardt, Stefan; Stolzer, Iris; Phu, Tuan Anh; Ng, Martin; Vu, Ngan K.; Tenzer, Stefan; Distler, Ute; et al.
Abstract: The intestinal microbiota influences mammalian host physiology in health and disease locally in the gut but also in organs devoid of direct contact with bacteria such as the liver and brain. Extracellular vesicles (EVs) or outer membrane vesicles (OMVs) released by microbes are increasingly recognized for their potential role as biological shuttle systems for inter‐kingdom communication. However, physiologically relevant evidence for the transfer of functional biomolecules from the intestinal microbiota to individual host cells by OMVs in vivo is scarce. By introducing Escherichia coli engineered to express Cre‐recombinase ( E. coli Cre ) into mice with a Rosa26.tdTomato ‐reporter background, we leveraged the Cre‐LoxP system to report the transfer of bacterial OMVs to recipient cells in vivo. Colonizing the intestine of these mice with E. coli Cre, resulted in Cre‐recombinase induced fluorescent reporter gene‐expression in cells along the intestinal epithelium, including intestinal stem cells as well as mucosal immune cells such as macrophages. Furthermore, even far beyond the gut, bacterial‐derived Cre induced extended marker gene expression in a wide range of host tissues, including the heart, liver, kidney, spleen, and brain. Together, our findings provide a method and proof of principle that OMVs can serve as a biological shuttle system for the horizontal transfer of functional biomolecules between bacteria and mammalian host cells.